Mental Health Research During the COVID-19 Pandemic: Focuses and Trends - Liang, Yaodong; Sun, Li; Tan, Xin (Frontiers in Public Health, 2022)
Abstract Objective: The COVID-19 pandemic has brought profound influence to the world. Wave after wave, many countries have been attacked by the pandemic which has caused social instability, hindered economic globalization, and harmed mental health. Though global academia has launched many types of research on mental health issues, the researches which focuses on mental health problems coursed by the COVID-19 pandemic is still at its starting stage. Based on the existing literature, we used bibliometric tools to conduct an overall analysis of mental health research during the COVID-19 pandemic. Method: Researchers from Universities, hospitals, communities, and medical institutions around the world used questionnaires survey, telephone-based survey, online survey, cross-sectional survey, systematic review and meta-analysis, systematic umbrella review as their research methods. Papers from three academic databases, WOS, ProQuest and CNKI, are included. We systematically collected, sorted, and translated their previous research results, and used SiteSpac II & VOSviewers to conduct a bibliometric analysis for them. Result: The authors who published a large number of papers are generally from China, the United States of America, the United Kingdom, South Korea, Singapore, and Australia. Huazhong University of Science and Technology, Hong Kong Polytechnic University, Shanghai Jiao Tong University are the top 3 Institutions. The University of Toronto, Columbia University, and the University of Melbourne have played important roles in the research of mental health problems during COVID-19. The quantities of related research papers in the USA and China are significantly larger than all other countries, while the centrality indexes for the co-occurrence of Germany, Italy, England & Canada are higher.